The Common Good: Collaboration among Cultural Institutions in Maine - Routhier, Jessica (Maine Policy Review, 2015)
A mission to serve the common good has characterized Maine cultural life since the earliest years of the nineteenth century. Collaborative institutions and initiatives within the arts and cultural community have developed and evolved in service of that goal. From professional organizations such as the Maine Charitable Mechanics, Union of Maine Visual Artists, and Maine Archives and Museums; to exhibition initiatives such as the Maine biennials, the Maine Art Museum Trail, and the “Projects” of the Maine Curators’ Forum; to collections-based projects such as Maine Memory Network and the Langlais Art Trail, this article demonstrates how the state’s museums, historical societies, and other arts and cultural organizations work collaboratively and independently at the same time, to their own mutual benefit as well as that of the people of Maine.
Keywords: humanities; cultural institutions; collaboration; Maine